2017
DOI: 10.5296/jas.v5i3.11664
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Degradation Analysis on 4-year-old Culms of Cultivated Tropical Bamboo Bambusa Vulgaris

Abstract: The thermal degradation of matured 4-year-old culms of cultivated tropical bamboo Bambusa vulgaris was studied and analyzed. The analysis using the Fourier Transform Infrared Spectroscopy and Thermal Gravimetric Analysis revealed the presence of basic functional groups in the bamboo which consists mainly of ester, carbonyl, and hydroxyl groups. The chemicals present in the bamboo vary depending on the location of the samples taken from the bamboo culms. The moisture content and extractive were omitted in the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…The results of the FTIR test in this study found that a peak between 1440 and 1475 cm −1 indicates a CH 2 asymmetric stretch. A peak between 2880 and 2975 cm −1 shows a CH 3 symmetrical stretch [ 51 , 52 ]. FTIR test results showed the presence of symmetrical bending of CH 3 in specimens of 0, 10, 20, and 30% at peaks of 1373, 1335, 1332, and 1336 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The results of the FTIR test in this study found that a peak between 1440 and 1475 cm −1 indicates a CH 2 asymmetric stretch. A peak between 2880 and 2975 cm −1 shows a CH 3 symmetrical stretch [ 51 , 52 ]. FTIR test results showed the presence of symmetrical bending of CH 3 in specimens of 0, 10, 20, and 30% at peaks of 1373, 1335, 1332, and 1336 cm −1 , respectively.…”
Section: Resultsmentioning
confidence: 99%